Media Resistance : Protest, Dislike, Abstention - Syvertsen, Trine (Basingstoke Springer Nature, 2017)
media; communication; social media; technology; cultural politics; media law; policy
English
Keywords: Film, TV & radio; Information technology industries; media; communication; social media; technology; cultural politics; media law; policy